Inflation dynamics during the Financial Crisis in Europe: cross-sectional identification of long-run inflation expectations - Geraldine Dany-Knedlik; Oliver Holtemöller (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We investigate drivers of Euro area inflation dynamics using a panel of regional Phillips curves and identify long-run inflation expectations by exploiting the cross-sectional dimension of the data. Our approach simultaneously allows for the inclusion of country-specific inflation and unemployment-gaps, as well as time-varying parameters. Our preferred panel specification outperforms various aggregate, uni- and multivariate unobserved component models in terms of forecast accuracy. We find that declining long-run trend inflation expectations and rising inflation persistence indicate an altered risk of inflation expectations de-anchoring. Lower trend inflation, and persistently negative unemployment-gaps, a slightly increasing Phillips curve slope and the downward pressure of low oil prices mainly explain the low inflation rate during the recent years.
Keywords: C32; C33; E31; E5; 330; inflation dynamics; inflation expectations; trend inflation; nonlinear state space model; panel UCSV model; Euro area